Tackling ALT-positive neuroblastoma: is it time to redefine risk classification systems? A systematic review with IPD meta-analysis - Marta Avinent-Pérez; Frank Westermann; Samuel Navarro; Amparo López-Carrasco; Rosa Noguera (Neoplasia: An International Journal for Oncology Research)
Background: The heterogeneous prognosis in neuroblastoma, shaped by telomere maintenance mechanisms (TMMs), notably the alternative lengthening of telomeres (ALT) pathway, necessitates a refined risk classification for high-risk patients. Current systems often lack precision, hindering tailored treatment approaches. This individual participant data (IPD) meta-analysis of survival among ALT-positive patients aims to improve risk classification systems, enhancing therapeutic strategies and patient outcomes. Methods: Following PRISMA-IPD guidelines, we conducted a comprehensive review of neuroblastoma patients retrieved from PubMed, Scopus, and Embase databases until March-2024. Patients were stratified into ALT-positive and TMM-negative subgroups. Overall and event-free survival probabilities were evaluated. Results: In our cohort of 293 patients (156 ALT-positive, 137 TMM-negative) obtained from eight different studies, ALT-positive individuals displayed lower survival rates than TMM-negative patients. Non-stage 4 ALT-positive patients had reduced overall and event-free survival probabilities compared to their TMM-negative counterparts, indicating potential misclassification. Stage 4 ALT-positive patients similarly showed poorer survival outcomes than non-stage 4 TMM-negative patients, underscoring the significance of ALT in patient prognosis. Conclusions: Our study highlights poorer outcomes in ALT-positive neuroblastoma patients, emphasizing the need to integrate TMM status into international risk classification guidelines. Standardizing TMM assessment is key for refining treatment strategies, considering the unique biology of ALT-positive patients.